Importance of 6 minute walk test in diagnostics of rare metabolic myophaty a case report - Natalija Angelkova; Elena Shukarova Angelkova; Mirjana Kocova; Filip Duma; Vesna Sabolic; Hristina Mandzukovska (Институт за јавно здравје на Република Македонија = Institute of public health of Republic of Macedonia, 2017)
Diagnosisi of rare inherited neuromuscular disorders is sometimes delayed due to variations in time of onset, different clinical appearance and limited diagnostic possibilites. The manegement of patients starts with neurological examinations followed by specific laboratory tests and neurological assesement. In the era of molecular medicine, molecular biology tools are useful in avoding some of the the invasive investigation such as muscle biopsy.We present a boy with a mild form of metabolic myopathy due to carnitine palmitoyltransferase 2 deficiency diagnosed upon timed functional assesment.A child had delayed developmental milestones,associated with fatigue and muscle pain during exercising and longer walks.There were no episodes of myoglobrinuira during exercise or during febrile illnesses.Neurological examination reveed proximal muscle weakness.Serum creatine kinase (CK) and serum lactate were above normal limits.Serum acylcarnitine profile was normal.Short timed functional tests such as 10 meters walk/run test showed normal results.Nord Star Amublatory Assesment showed difficulties in balance and jumping.Diagnosis of myopathy was suspected after performance of 6-minute walk test, when the passed distance was 327 meters with slowing and fatigue.EMG and echocardiography were within normal range.Diagnosis was established by equencing of the CPT II gene which revealed c.338C>T (p.Ser113Leu) mutation in homozygous form as characteristic CPT II deficiency profile.